Editorial for the Special Issue “Functionalized Gels for Environmental Applications 2nd Edition” - Luca Burratti; Iole Venditti; Paolo Prosposito (Gels, 2025)
Dear readers, the second edition of the Special Issue entitled “Functionalized Gels for Environmental Applications” in the journal Gels was also a great success [...]